Peran Media Sosial dalam Meningkatkan Kunjungan Wisatawan ke Situs Cagar Budaya Batu Go’ong di Citaman - Sandi Hardiansyah; Munawaroh Munawaroh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Indonesia is a country with diverse culture and tourism. The rapid development of technology causes changes. Sukaraja village has religious tourism potential which has not been utilized optimally through social media. The BATU GOONG Cultural Heritage Site and its MSME actors are one of the main attractions, but have not utilized platforms such as Instagram, TikTok, Facebook and Twitter for promotion. Therefore, there are three stages of activity plans which include training on creating social media accounts, tourism and MSME digitalization seminars, as well as developing Instagram and Facebook content. These three stages aim to increase the promotion of Batu Goong religious tourism so that there will be an increase in visitors.